FC 073REGIONAL EFFICACY AND SAFETY RESULTS OF ROXADUSTAT COMPARED WITH PLACEBO OR DARBEPOETIN ALFA IN NON-DIALYSIS-DEPENDENT (NDD) CHRONIC KIDNEY DISEASE (CKD) PATIENTS WITH ANAEMIA. (29th May 2021) - Dimkovic, Nada; Esposito, Ciro; Barratt, Jonathan; Mariat, Christophe; Shutov, Evgeny; Reusch, Michael; Young, James; Sulowicz, Wladyslaw
Abstract: Background and Aims: Roxadustat regulates erythropoiesis and iron metabolism through hypoxia-inducible factor prolyl hydroxylase inhibition. This regional analysis evaluated efficacy and safety for roxadustat versus placebo/darbepoetin alfa (DA) in NDD CKD patients with anaemia. Method: Results from three, double-blind phase 3 studies comparing roxadustat to placebo (ALPS, ANDES, OLYMPUS) in patients with anaemia and stage 3-5 NDD CKD were pooled and evaluated alongside results of an open-label study comparing roxadustat to DA (DOLOMITES) in the same population. Efficacy outcomes were compared in three regions (Europe, US, and other) in placebo-controlled studies (PCS) and two regions (Western Europe/Israel and Central/Eastern Europe) in the DA-controlled study (DCS). The primary efficacy endpoint in Europe was haemoglobin (Hb) response, defined as Hb ≥11.0 g/dL that changed from baseline (CFB) by ≥1.0 g/dL in patients with Hb >8.0 g/dL or as CFB ≥2.0 g/dL in patients with Hb ≤8.0 g/dL. The secondary efficacy endpoint was Hb CFB to Weeks 28-36 without rescue therapy (intravenous iron, red blood cell [RBC] transfusion, or erythropoiesis-stimulating agent [ESA] for PCS; RBC transfusion or ESA [roxadustat only] for DCS). Incidence of treatment-emergent adverse events (TEAEs) was summarised descriptively in two regions in PCS (Europe and non-Europe) and two regions in DCS (Western Europe/Israel and Central/Eastern Europe). Results: A total of 4886 patients were randomised (2709 roxadustat; 1884 placebo; 293 DA). A significantly greater proportion of patients in all regions who received roxadustat had a Hb response without rescue therapy vs placebo (Europe: 77.9% vs 16.5%, difference of proportion [DOP] 61.4%, 95% CI: 56.5-66.2; US: 75.4% vs 8.3%, DOP 67.2%, 95% CI: 62.7-71.6; and other: 83.4% vs 5.5%, DOP 78.0%, 95% CI: 75.4-80.5) and a numerically greater proportion in both regions vs DA (Western Europe/Israel: 93.9% vs 83.5%, DOP 10.4%, 95% CI: 1.2-19.6; Central/Eastern Europe: 86.5% vs 75.4%, DOP 10.9%, 95% CI: 3.6-18.3). Mean Hb CFB was significantly greater with roxadustat vs placebo in Europe (2.01 vs 0.37 g/dL, LSMD 1.70, 95% CI: 1.55-1.84), US (1.80 vs 0.21 g/dL, LSMD 1.67, 95% CI: 1.53-1.82), and other (1.80 vs 0.06 g/dL, LSMD 1.77, 95% CI: 1.64-1.89) (all P<0.0001) and similar vs DA in Western Europe/Israel (1.64 vs 1.75 g/dL, LSMD -0.03, 95% CI: -0.30 to 0.23, P=0.80) and Central/Eastern Europe (1.94 vs 1.88 g/dL, LSMD 0.03, 95% CI: -0.14 to 0.21, P=0.72). The range in incidence for select TEAEs (arteriovenous fistula thrombosis, deep vein thrombosis, nausea, and seizure) was: 0.3-8.4% for roxadustat and 0.2-4.3% for placebo in Europe; 0.8-10.8% for roxadustat and 0.1-7.0% for placebo in non-Europe; 0-12.1% for roxadustat and 0-11.8% for DA in Western Europe/Israel; 0.4-6.3% for roxadustat and 0-3.4% for DA in Central/Eastern Europe. Conclusion: In patients with anaemia and stage 3-5 NDD CKD, roxadustat was more effective than placebo for correcting Hb and generating Hb response without rescue therapy in Europe, the US, and other countries. It was similarly effective as DA for correcting Hb and generating a Hb response without rescue therapy in Western Europe/Israel and Central/Eastern Europe. The incidence of select TEAEs was comparable and relatively low in all regions.